Fort Oranje. An inventory of historical and archaeological information with respect to Fort Oranje in 'Dutch Brazil' (Bulletin KNOB, 2002)
Along the Northeast coast of Brazil, fortresses and fortifications were built by the Dutch at strategic locations and the fortresses conquered from the Portuguese were strengthened and expanded. In total 39 fortresses and fieldworks were built in 'New Holland', which indicates that a good defense was considered very important. In order to be able to execute the plans for this 'Atlantic Wall' in 'the New World' materials and architects were brought along from the mother country.However, the colony only existed for a short while. Internal controversies, profits from the sugar production that failed to materialise, and receding investments of the WIC were some of the causes. Moreover, with the dwindling Dutch power the opposition of the Portuguese increased dramatically. In 1654 'Dutch Brazil' was passed on to the Portuguese forces.It is clear that Fort Oranje knew several building phases. It is likely that there was a first building phase of a fieldwork in sand and loam. Later this was strengthened with timber stockades and stone constructions. Frans Post possibly represented the first building phase in 1637, and in the version of 1645 in 'Barlaeus' a second phase with stockades. The large blocks of lime-stone, from which the walls of the fortress are now constructed, probably date back to the Portuguese period. Historical-archaeological research may lead to greater clarity on the building history of the fortress.Traces of the Dutch fortress, such as the loam and timber of the walls, the barracks, the brick sallyport, the ditch, the hornwork, a graveyard and a cesspit have not been recovered so far. In 1970 the Laboratório de Arquelogia of the Universidade Federal de Pernambuco already executed a superficial excavation in the fortress, most of which was then still concealed below the sand.From January through March 2002 the same Laboratório executed a new excavation campaign in Fort Oranje in co-operation with the University of Amsterdam and the Foundation for Exploration and Conservation of Monuments of the Dutch West India Company (MOWIC Foundation).Thus below ground, level remnants of the walls of a Dutch ammunition room were found on the east side of the inner courtyard. They consist of neat masonry, in cross bond and in English bond, of Dutch red and yellow bricks. The map from 'Barlaeus' confirms the location. In addition, part of the well was excavated. Research into other Dutch remnants is to be continued in a second and last campaign end 2002. The results are already expected in 2003, so that they can be taken into account for the forthcoming restoration of the fortress.